2020
DOI: 10.1590/s2179-975x7619
|View full text |Cite
|
Sign up to set email alerts
|

Climate change reflected in one of the largest wetlands in the world: an overview of the Northern Pantanal water regime

Abstract: The dynamics of Pantanal is totally influenced by the flood pulse, which is, in part, a consequence of rainfall regime from the Amazon in the direction to the headlands and the lowlands where the water is retained, and the flood plain is formed. The impacts of climate change have not yet been measured for the Northern Pantanal (Pantanal of Cáceres), where it is the gateway to most Pantanal waters. Here, we have used rainfall, hydrology, and satellite imagery data to ascertain the possible rainfall patterns, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 28 publications
0
24
0
7
Order By: Relevance
“…The temporal displacement of precipitation, starting later and ending earlier, with some places indicating a reduction in rainfall, was observed from the south of the Amazon Forest to the Pantanal (Debortoli et al, 2012). Likewise, a reduction in the water mass in the Pantanal was also recorded (Lázaro et al 2020;MapBiomas, 2021). A study of MapBiomas (2021) indicated that, from 1985 to 2020, the Pantanal had a 68% reduction of its water surface, and that Poconé was the fourth municipality in Brazil in the proportion of lost water surface in the past 30 years.…”
Section: Discussionmentioning
confidence: 91%
“…The temporal displacement of precipitation, starting later and ending earlier, with some places indicating a reduction in rainfall, was observed from the south of the Amazon Forest to the Pantanal (Debortoli et al, 2012). Likewise, a reduction in the water mass in the Pantanal was also recorded (Lázaro et al 2020;MapBiomas, 2021). A study of MapBiomas (2021) indicated that, from 1985 to 2020, the Pantanal had a 68% reduction of its water surface, and that Poconé was the fourth municipality in Brazil in the proportion of lost water surface in the past 30 years.…”
Section: Discussionmentioning
confidence: 91%
“…This is true for Pantanal, Earth's largest wetland. Focusing on Northern Pantanal, Lázaro et al (2020) discussed the consequences of an increase in the number of dry days over a timeseries of 42 years. According to them, the Northern Pantanal had an increase in 13% of dry days and a loss in the water mass of about 16% considering the past 10 years.…”
mentioning
confidence: 99%
“…In fact, permanent fire brigades have been established, and an animal rescue centre is under construction in response to the effects of the recent extensive fires in the Pantanal. Although actions are underway at local levels, the warming and drying trend 19,21,34,35 is also a combination of global warming 34,36 and rapid land-use changes 15,25,42 (SI_Figs.S5), with cumulative impacts in the UPRB and Pantanal wetlands (SI_Fig.S1). Therefore, the immediate reduction of deforestation in the Amazon and Pantanal and the establishment of a forest restoration plan in the UPRB are critical.…”
Section: Discussionmentioning
confidence: 99%